The role of the compensation lawsuit in protecting the right of individuals from the arbitrariness of manaement - حيدر, رنا (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The responsibility of the administration raises many problems, especially its responsibility for its activity without error. Many countries have adopted this responsibility in their legislation and included it in their judicial rulings as a form of achieving justice and redress for the oppressed affected by the activity of the administration despite not committing any mistake. Most of the Arab countries did not follow this path and did not adopt the risk theory despite its importance, and this is what makes us ask the following question: To what extent does the annulment suit achieve adequate protection for individuals in the face of the administration with the complementary full judicial lawsuit that is filed to compensate for the damages resulting from the illegal actions of the administration, in light of not raising its responsibility in the absence of error, especially since there are many cases where the damage is caused to some Individuals seriously harmed, who compensates them?